Integrasi RBAC, AES-256, dan Audit-log untuk Keamanan dan Auditabilitas Sistem Inventori UMKM - Andik Prakasa Hadi; Singgih Aliana Winastuti; Ahmad Zainudin (Sekolah Tinggi Manajemen Informatika dan Komputer AUB - Indonesia, 2026)
Micro and small enterprises face inventory management issues, including stock recording errors, weak access control, and lack of data change traceability. This study develops a web-based inventory system integrating Role-Based Access Control (RBAC), AES-256 encryption, and audit logs. The system was built using the Laravel framework with a Design Science Research (DSR) approach. Functional testing achieved a 100% success rate. Usability evaluation using the System Usability Scale (SUS) with six respondents produced a mean score of 87.5 (excellent category). AES-256 encryption effectively protects sensitive data, while audit logs support system accountability. Verification also confirms compliance with the NIST SP 800-171 standard. This study contributes an integrated three-mechanism security system ready for adoption by garment-sector SMEs.